Preparation method of sulfur antimony selenide solar cell with uniform absorption layer component gradient
By using triethanolamine in the hydrothermal method to adjust the reaction kinetics of the Sb2(S,Se)3 film, the problems of uneven distribution of longitudinal components and unstable energy band structure are solved, and the efficiency of antimony sulfide selenide solar cells is significantly improved.
Patent Information
- Application Number
- CN202411836026.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The longitudinal components of the Sb2(S,Se)3 films were prepared under hydrothermal method, which resulted in limited carrier transmission performance and unstable energy band structure, affecting the efficiency of solar cells.
Triethanolamine is used as a complexing agent to regulate the reaction kinetics of Sb2(S,Se)3 films, optimize the proportional distribution of longitudinal Se/(S+Se) elements, reduce energy band offset, and promote the formation of uniform energy band gradients.
The uniformity of the longitudinal component distribution of Sb2(S,Se)3 film and the stability of the energy band structure are achieved, and the photocurrent and efficiency of the solar cell are improved, from 8.75% to 9.94%.
Smart Images

Figure CN119654036A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of antimony sulfoselenide solar cells, and particularly relates to a preparation method of an antimony sulfoselenide solar cell with a uniform absorption layer composition gradient. Background Art
[0002] Antimony sulfoselenide (Sb2(S x Se 1-x )3, 0 < x < 1) has been widely studied and developed in the fields of photovoltaic devices, photocatalytic water splitting, photodetectors, indoor photovoltaics, energy storage, etc. due to its high stability, simple composition, abundant reserves, excellent optoelectronic properties, high theoretical power conversion efficiency, etc. Especially in the applications of flexible or tandem devices related to Sb2(S x Se 1-x )3 thin film solar cells, it has shown excellent performance and great development prospects. Among them, the Sb2(S,Se)3 alloy has excellent properties such as a quasi-one-dimensional ribbon structure, a high absorption coefficient (>10 5 cm -1 ) and an adjustable bandgap (1.1 eV - 1.7 eV). According to the Shockley-Queisser (S-Q) limit theory, by adjusting the Se / (S+Se) ratio of the Sb2(S,Se)3 thin film, a photoelectric conversion efficiency of more than 30% can be achieved. At present, the hydrothermal method is considered to be one of the most effective methods for preparing high-efficiency Sb2(S,Se)3 solar cells. The highest efficiency of Sb2(S,Se)3 solar cells prepared based on the hydrothermal method has reached 10.81%, but there is still a large gap with the theoretical efficiency. Based on the hydrothermal deposition method, in the preparation of high-quality Sb2(S,Se)3 thin films, researchers have improved the quality of Sb2(S,Se)3 thin films through methods such as additives (such as EDTA and NH4F), post-treatment (such as alkali metal solutions), backside etching or modification. However, due to the problem of uneven longitudinal component distribution of the thin film caused by uncontrollable reaction kinetics, there is still a lack of effective solutions, which will seriously limit the lattice orientation and band structure of subsequent devices, and further limit the improvement of carrier transport performance. As is well known, efficient carrier transport is crucial for reducing non-ideal carrier recombination losses in thin film solar cells. Therefore, studying the formation mechanism of Sb2(S,Se)3 thin films with good performance is of great significance for improving carrier transport in Sb2(S,Se)3 thin film solar cells based on the hydrothermal method. However, due to the different reaction activities of Se 2+ and S 2+ with Sb 3+ (Se 2+ is more active than S 2+ ), the stability of Sb2S3 precipitation (K SP = 10 -90 ) is higher than that of Sb2Se3 (KSP = 10 -113 ) precipitation has poor stability. Therefore, especially for the sodium selenium sulfate system, process parameters such as reaction temperature and holding time will have a great influence on the component distribution of the precursor film and cause the band gap fluctuation of the Sb2(S,Se)3 film, which will greatly limit the carrier transport of Sb2(S,Se)3 thin film solar cells. In order to obtain high-performance Sb2(S,Se)3 thin film solar cells under the hydrothermal method, an effective method is urgently needed to regulate the non-ideal deposition process. Seeking a more effective strategy to make the longitudinal composition of the Sb2(S,Se)3 film controllable and uniform, thereby suppressing the carrier recombination loss caused by the non-ideal energy band arrangement, is currently the key direction for realizing high-efficiency Sb2(S,Se)3 thin film solar cells. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing an antimony sulfide selenide solar cell with a uniform absorption layer component gradient.
[0004] In view of the above problems, the present invention solves the following two technical problems: (1) An optimization scheme was proposed to improve the uniformity of the longitudinal component distribution of Sb2(S,Se)3 thin films and the energy band matching of Sb2(S,Se)3 devices by using a low-cost triethanolamine complexing agent, which solved the problem of Se in the hydrothermal reaction system. 2+ Same as Sb 3+ The problem of unsatisfactory longitudinal component gradient in the absorption layer caused by too rapid reaction precipitation.
[0005] (2) Revealing the intrinsic mechanism of triethanolamine regulating the hydrothermal reaction kinetics of Sb2(S,Se)3 and improving the conversion efficiency of the device. This laid an important theoretical and experimental foundation for the development of controllable Sb2(S,Se)3 hydrothermal reaction and provided valuable reference for the subsequent preparation of high-quality Sb2(S,Se)3 thin films.
[0006] The introduction of triethanolamine has the following advantages: 1. It realizes the time domain control of the reaction process and optimizes the Se / (S+Se) element ratio distribution of the Sb2(S,Se)3 film; 2. It suppresses the energy band fluctuation of the Sb2(S,Se)3 device, so that the Sb2(S,Se)3 film forms a uniform energy band gradient, thereby reducing the minority carrier recombination and improving the photocurrent of the Sb2(S,Se)3 solar cell; 3. It improves the vertical growth orientation of the Sb2(S,Se)3 film and promotes the carrier transport of the device.
[0007] The specific technical solutions of the present invention are as follows: ① FTO substrate cleaning: The FTO substrate was ultrasonically cleaned with ethanol, acetone, and deionized water to remove stains on the substrate surface. After the ultrasonic cleaning, the surface moisture of the substrate was blown dry with an air gun for later use; ② Deposition of CdS film: Mix deionized water, CdSO4 and ammonia water, and then heat at 66 °C for 2 min. After that, add thiourea and stir to mix evenly. Finally, put the FTO substrate and heat and deposit for 22 min. Then take out the substrate and blow dry for later use. ③CdCl2 treatment: CdCl2 was dissolved in methanol, and then the CdCl2 solution was spin-coated on the CdS film using a coating machine. After the spin coating, the substrate was placed on a hot plate at 400 °C and annealed in an air environment for 11 minutes. After the annealing, it was cooled for use; ④ Preparation of sodium selenosulfate solution: Pour 0.3158 g of selenium powder and 2.0166 g of anhydrous sodium sulfite into a hydrothermal kettle and add 80 mL of deionized water. Then put the hydrothermal kettle into a constant temperature magnetic stirring heating jacket and perform a hydrothermal reaction at 130 °C for 8 hours. After the reaction is completed and cooled, filter it with a filter syringe for later use; ⑤ Preparation of Sb2(S,Se)3 absorption layer: The sample treated with CdCl2 was attached to a glass slide with high-temperature double-sided tape, and then 0.2671 g potassium antimony tartrate trihydrate, 1.5884 g sodium thiosulfate pentahydrate and 120 mg triethanolamine were dissolved in 10 mL, 10 mL and 20 mL deionized water respectively, and then the three solutions were mixed and stirred until the solution turned yellow, followed by adding 5 mL of sodium selenosulfate solution. After stirring for 1 min, the carrier was placed obliquely into a polytetrafluoroethylene liner and the mixed solution was poured in; then the polytetrafluoroethylene liner was placed in a hydrothermal autoclave and then placed in an oven at 130 ° C for 3 hours. After the reaction was completed, the film surface was rinsed with deionized water and blown dry after cooling. Finally, the sample was placed on a hot plate at 360 ° C in a nitrogen atmosphere glove box for 10 min annealing to improve the crystallinity of the film; ⑥Preparation of Spiro-OMeTAD hole transport layer: The spin coater was set to single-step operation mode, with a speed of 3500 rpm, a time of 30 s, and an acceleration of 1000 rpm / s; 20 uL of the prepared Spiro-OMeTAD solution was extracted with a pipette and dropped onto the sample. After spin coating, annealing was performed on a hot plate at 105 °C for 10 min; ⑦ Evaporation of Au electrode: The gold electrode is prepared by thermal evaporation. The mask is placed in the evaporation machine and the Au evaporation program is run. Finally, the surface of the device is divided into two sections with the same effective area of 0.09 cm 2 of small squares.
[0008] The advantages of the present invention are: The efficiency of antimony sulfide selenide (Sb2(S,Se)3) solar cells based on the hydrothermal method has exceeded 10.0%. However, due to the difference in reactivity between selenium and selenium sources, that is, the uncontrollability of the hydrothermal process, the preparation of high-quality Sb2(S,Se)3 films has become a bottleneck for high-efficiency Sb2(S,Se)3 solar cells. The present invention innovatively uses triethanolamine chelating agent to regulate the reaction kinetics of Sb2(S,Se)3 films. The results show that triethanolamine chelating agent can realize the time domain control of the reaction process, optimize the longitudinal Se / (S+Se) element ratio distribution of Sb2(S,Se)3 films, reduce the energy band offset of Sb2(S,Se)3 devices, and promote the formation of a uniform energy band back gradient in Sb2(S,Se)3 films, thereby reducing the minority carrier recombination at the back contact, increasing the photocurrent of Sb2(S,Se)3 solar cells, and reducing the diode leakage current. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 (a) Sb2(S,Se)3 solar cell under AM 1.5 light JV curve, (b) EQE curve of Sb2(S,Se)3 solar cell; Figure 2 (a) SEM images of Sb2(S,Se)3 films without and with TEA added (b), (c) XRD patterns of Sb2(S,Se)3 films without and with TEA added. DETAILED DESCRIPTION
[0010] In order to make the above features and advantages of the present invention more clearly understood, the following embodiments are given for detailed description. The methods of the present invention are all conventional methods in the art unless otherwise specified.
[0011] Example 1 ① FTO substrate cleaning: First, scrub the FTO substrate clean with detergent, then put the substrate into a beaker and ultrasonicate it in an ultrasonic machine for 30 minutes with ethanol, acetone, and deionized water respectively to remove stains on the substrate surface. After the ultrasonication, use an air gun to blow dry the moisture on the substrate surface for later use.
[0012] ② Deposition of CdS thin film: First, pour 220 mL of deionized water, 32 mL of 15 mM CdSO4 solution and 42 mL of 28 wt% ammonia water into a beaker and mix them. Then heat the beaker in a 66°C water bath for 2 min. After that, pour in 16 mL of 1.5 mM thiourea aqueous solution and stir to mix evenly. Finally, place the FTO substrate in a 66°C heating deposition chamber for 22 min. Then take out the substrate and blow dry it for later use.
[0013] ③CdCl2 treatment: Dissolve 15 mg CdCl2 in 1 mL methanol, and then use a coater to spin coat the CdCl2 solution on the CdS film. After spin coating, place the substrate on a 400 °C hot plate and anneal in an air environment for 11 minutes. After annealing, let it cool down for use.
[0014] ④ Preparation of sodium selenosulfate solution: Pour 0.3158 g of selenium powder and 2.0166 g of anhydrous sodium sulfite into a hydrothermal kettle and add 80 mL of deionized water. Then put the hydrothermal kettle into a constant temperature magnetic stirring heating jacket and carry out a hydrothermal reaction at 130 °C for 8 hours. After the reaction is completed and cooled, filter it with a filter syringe for later use.
[0015] ⑤ Preparation of Sb2(S,Se)3 absorption layer: The sample treated with CdCl2 was attached to a glass slide with high-temperature double-sided tape, and then 0.2671 g potassium antimony tartrate trihydrate, 1.5884 g sodium thiosulfate pentahydrate and 120 mg triethanolamine were dissolved in 10 mL, 10 mL and 20 mL deionized water respectively. Then the three solutions were mixed and placed on a magnetic stirrer for stirring until the solution turned yellow. Then 5 mL of sodium selenosulfate solution was added. After stirring for 1 min, the carrier was placed obliquely in a polytetrafluoroethylene liner and the mixed solution was poured in. Then the polytetrafluoroethylene liner was placed in a hydrothermal autoclave and then placed in an oven at 130 °C for reaction for 3 hours. After the reaction was completed, the film surface was rinsed with deionized water and blown dry after cooling. Finally, in a glove box with a nitrogen atmosphere, the sample was placed on a hot plate at 360 °C for 10 min annealing to improve the crystallinity of the film.
[0016] ⑥ Preparation of Spiro-OMeTAD hole transport layer: The spin coater was set to single-step operation mode, with a rotation speed of 3500 rpm, a time of 30 s, and an acceleration of 1000 rpm / s; 20 uL of the prepared 36.6 mg / mL Spiro-OMeTAD solution was drawn with a pipette and dropped onto the sample. After spin coating, annealing was performed on a hot plate at 105 °C for 10 min.
[0017] ⑦ Evaporation of Au electrode: The gold electrode is prepared by thermal evaporation. The mask is placed in the evaporation machine and the Au evaporation program is run. Finally, the surface of the device is divided into two sections with the same effective area of 0.09 cm 2 of small squares.
[0018] Comparative Example 1 ① FTO substrate cleaning: First, scrub the FTO substrate clean with detergent, then put the substrate into a beaker and ultrasonicate it in an ultrasonic machine for 30 minutes with ethanol, acetone, and deionized water respectively to remove stains on the substrate surface. After the ultrasonication, use an air gun to blow dry the moisture on the substrate surface for later use.
[0019] ② Deposition of CdS thin film: First, pour 220 mL of deionized water, 32 mL of 15 mM CdSO4 solution and 42 mL of 28wt% ammonia water into a beaker and mix them. Then heat the beaker in a 66°C water bath for 2 min. After that, pour in 16 mL of 1.5 mM thiourea aqueous solution and stir to mix evenly. Finally, place the FTO substrate in a 66°C heating deposition chamber for 22 min. Then take out the substrate and blow dry it for later use.
[0020] ③CdCl2 treatment: Dissolve 15 mg CdCl2 in 1 mL methanol, and then use a coater to spin coat the CdCl2 solution on the CdS film. After spin coating, place the substrate on a 400 °C hot plate and anneal in an air environment for 11 minutes. After annealing, let it cool down for use.
[0021] ④ Preparation of sodium selenosulfate solution: Pour 0.3158 g of selenium powder and 2.0166 g of anhydrous sodium sulfite into a hydrothermal kettle and add 80 mL of deionized water. Then put the hydrothermal kettle into a constant temperature magnetic stirring heating jacket and carry out a hydrothermal reaction at 130 °C for 8 hours. After the reaction is completed and cooled, filter it with a filter syringe for later use.
[0022] ⑤ Preparation of Sb2(S,Se)3 absorption layer: The sample treated with CdCl2 was attached to a glass slide with high-temperature double-sided tape, and then 0.2671 g potassium antimony tartrate trihydrate and 1.5884 g sodium thiosulfate pentahydrate were dissolved in 10 mL and 20 mL deionized water respectively. The two solutions were mixed and placed on a magnetic stirrer for stirring until the solution turned yellow. Then 5 mL of sodium selenosulfate solution was added. After stirring for 1 min, the carrier was placed obliquely in a polytetrafluoroethylene liner and the mixed solution was poured in. Then the polytetrafluoroethylene liner was placed in a hydrothermal autoclave and then placed in an oven at 130 °C for reaction for 3 hours. After the reaction was completed, the film surface was rinsed with deionized water and blown dry after cooling. Finally, in a glove box with a nitrogen atmosphere, the sample was placed on a hot plate at 360 °C for 10 min annealing to improve the crystallinity of the film.
[0023] ⑥ Preparation of Spiro-OMeTAD hole transport layer: The spin coater was set to single-step operation mode, with a rotation speed of 3500 rpm, a time of 30 s, and an acceleration of 1000 rpm / s; 20 uL of the prepared 36.6 mg / mL Spiro-OMeTAD solution was drawn with a pipette and dropped onto the sample. After spin coating, annealing was performed on a hot plate at 105 °C for 10 min.
[0024] ⑦ Evaporation of Au electrode: The gold electrode is prepared by thermal evaporation. The mask is placed in the evaporation machine and the Au evaporation program is run. Finally, the surface of the device is divided into two sections with the same effective area of 0.09 cm 2 of small squares.
[0025] The efficiency of antimony sulfide selenide (Sb2(S,Se)3) solar cells based on the hydrothermal method has exceeded 10.0%. However, due to the reactivity difference between selenium and the selenium source, that is, the uncontrollability of the hydrothermal process, the preparation of high-quality Sb2(S,Se)3 films has become a bottleneck for high-efficiency Sb2(S,Se)3 solar cells. The present invention innovatively uses triethanolamine chelating agent to regulate the reaction kinetics of Sb2(S,Se)3 films. The results show that triethanolamine chelating agent can realize time domain control of the reaction process, optimize the longitudinal Se / (S+Se) element ratio distribution of Sb2(S,Se)3 films, reduce the energy band offset of Sb2(S,Se)3 devices, and promote the formation of a uniform energy band back gradient in Sb2(S,Se)3 films, thereby reducing the minority carrier recombination at the back contact, increasing the photocurrent of Sb2(S,Se)3 solar cells, and reducing the diode leakage current. From Figure 1 As can be seen in (b), after the introduction of TEA, the external quantum efficiency of the Sb2(S,Se)3 film in the 300-1100nm band has been significantly improved, proving that TEA effectively improves the orientation and film quality of the Sb2(S,Se)3 film, thereby improving its photoresponse. In order to verify the improvement of film quality and orientation, the Sb2(S,Se)3 film was characterized by SEM and XRD ( Figure 2), it can be seen that: 1) Due to the introduction of TEA, the Sb2(S,Se)3 absorption layer film is more uniform and flat, and the antimony oxide secondary phase on the surface of the film is suppressed; 2) The (021) and (061) preferred orientations of the Sb2(S,Se)3 absorption layer film are enhanced. Finally, under the optimization of TEA, the short-circuit current density and fill factor of the Sb2(S,Se)3 solar cell are significantly improved, and its photoelectric conversion efficiency is increased from 8.75% to 9.94%. From the above JV, EQE, SEM and XRD analysis results, it can be seen that the introduction of TEA effectively regulates the reaction kinetics of the hydrothermal deposition process of the Sb2(S,Se)3 film, making the longitudinal Se / (S+Se) element ratio distribution of the film more uniform, thereby improving the quality of the Sb2(S,Se)3 film and enhancing the (hk1) orientation of the Sb2(S,Se)3 film. These optimizations lead to smaller band offsets in Sb2(S,Se)3 devices and more uniform back gradients in Sb2(S,Se)3 films, which reduces minority carrier recombination at the back contact and ultimately improves the photoelectric conversion efficiency of Sb2(S,Se)3 solar cells. This is one of the highest values of Sb2(S,Se)3 solar cells using a sodium thiosulfate system to date. This will promote the industrialization of low-cost antimony sulfide selenide compound thin-film solar cells and provide valuable reference for the homogenization of components and the regulation of reaction kinetics of antimony-based chalcogenide solar cells.
[0026] Table 1 Performance parameters of Sb2(S,Se)3 solar cells under Control and TEA conditions The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing an antimony sulfide selenide solar cell with a uniform absorption layer component gradient, characterized in that: The following steps are involved: ①FTO substrate cleaning; ②Deposition of CdS thin film; ③CdCl2 treatment: CdCl2 was dissolved in methanol, and then the CdCl2 solution was spin-coated on the CdS film using a coating machine. After the spin coating, the substrate was placed on a hot plate at 400 °C and annealed in an air environment for 11 min. After the annealing, it was cooled for use; ④ Preparation of sodium selenosulfate solution: Pour selenium powder and anhydrous sodium sulfite into a hydrothermal kettle and add deionized water. Then put the hydrothermal kettle into a constant temperature magnetic stirring heating jacket and perform a hydrothermal reaction at 130 °C for 8 hours. After the reaction is completed and cooled, filter it with a filter syringe for later use; ⑤ Preparation of Sb2(S,Se)3 absorption layer: The sample treated with CdCl2 was attached to a glass slide with high-temperature double-sided tape, and then 0.2671 g potassium antimony tartrate trihydrate, 1.5884 g sodium thiosulfate pentahydrate and 120 mg triethanolamine were dissolved in 10 mL, 10 mL and 20 mL deionized water respectively, and then the three solutions were mixed and stirred until the solution turned yellow, followed by adding 5 mL of sodium selenosulfate solution. After stirring for 1 min, the carrier was placed obliquely into a polytetrafluoroethylene liner and the mixed solution was poured in; then the polytetrafluoroethylene liner was placed in a hydrothermal autoclave, and then placed in an oven at 130 °C for reaction for 3 hours. After the reaction was completed, the film surface was rinsed with deionized water after cooling and blown dry. Finally, in a glove box with a nitrogen atmosphere, the sample was placed on a hot plate at 360 °C for 10 min for annealing to improve the crystallinity of the film; ⑥Preparation of Spiro-OMeTAD hole transport layer; ⑦Evaporated Au electrode.
2. The preparation method according to claim 1, characterized in that: The operation of cleaning the FTO substrate in step ① specifically includes: ultrasonically cleaning the FTO substrate with ethanol, acetone, and deionized water to remove stains on the substrate surface, and after the ultrasonic cleaning, using an air gun to blow dry the moisture on the substrate surface for later use.
3. The preparation method according to claim 1, characterized in that: The operation of depositing the CdS film in step ② specifically includes: mixing deionized water, CdSO4 and ammonia water, and then heating at 66°C for 2 min, adding thiourea and stirring to mix evenly, finally placing the FTO substrate and heating to deposit the CdS film, taking out the substrate and blowing it dry for use.
4. The preparation method according to claim 3, characterized in that: The heating deposition temperature in step ② is 66°C.
5. The preparation method according to claim 3, characterized in that: The deposition time in step ② is 22 min.
6. The preparation method according to claim 1, characterized in that: In step ④, during the preparation of the sodium selenosulfate solution, the amount of selenium powder used was 0.3158 g, the amount of anhydrous sodium sulfite used was 2.0166 g, and the amount of deionized water used was 80 mL.
7. The preparation method according to claim 1, characterized in that: The preparation of the Spiro-OMeTAD hole transport layer in step ⑥ specifically includes: setting the coater to a single-step operation mode, a rotation speed of 3500 rpm, a time of 30 s, and an acceleration of 1000 rpm / s; using a pipette to extract 20 uL of the prepared Spiro-OMeTAD solution, dripping it onto the sample, and after spin coating, annealing on a hot stage.
8. The preparation method according to claim 7, characterized in that: The annealing temperature in step ⑥ is 105°C.
9. The preparation method according to claim 7, characterized in that: The annealing time in step ⑥ is 10 min.
10. The preparation method according to claim 1, characterized in that: In step ⑦, the Au electrode is prepared by thermal evaporation, the mask is placed in the evaporation machine, and the Au evaporation program is run.
Citation Information
Patent Citations
Method for preparing copper-zinc-tin-sulfur-selenium film based on aqueous solution
CN105039937A
Solar cell absorption layer and preparation method and application thereof
CN110518081A
Ethoxylated n-alkyl glucamine prepn - and use in low-foaming washing, rinsing and cleaning agents
DE2200040A1
Method for preparing light absorption layer of copper-indium-gallium-sulfur-selenium thin film solar cells
US20110008927A1
Disubstituted-aminodifluorosulfinium salts, process for preparing same and method of use as deoxofluorination reagents
US20120108801A1